Peran Penting Hukum dalam Melindungi Desain Fashion Dalam Perspektif Perlindungan Kekayaan Intelektual - Mauliya Fitriani; Della Miftahurrizka; Mizan Imani Naqsyabandi; Noerma Kurnia Fajarwati (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2024)
Fashion design as a creative and intellectual expression requires appropriate legal protection to encourage innovation and protect the rights of creators. This article discusses the important role of law in protecting fashion design from an intellectual protection perspective. This approach involves an analysis of the role of intellectual property rights, especially copyright and industrial design, in providing adequate protection for works of art in the world of fashion. Copyright provides automatic protection for original works, including fashion designs. However, copyright restrictions result in limited protection, which is why it is important to understand how industrial designs can provide broader protection. Through industrial design registration, creators can secure exclusive rights to their fashion designs, preventing unauthorized duplication. This legal protection also helps create a fair business environment and fuels the growth of the fashion industry. By recognizing the economic and creative value of fashion design, the law plays a role in encouraging investment and innovation in the sector. Therefore, a deep understanding of the role of law in the intellectual protection of fashion design is crucial for interested industry players, creators and users.